CHEMICAL PROPERTIES, MICROBIOLOGY AND ANTIOXIDANT ACTIVITYOF ABON BEEF IN THE CITY OF PALU - Sukisman Abdul Halid; Abdul Rahim (Universitas Tadulako, 2018)
One of the most popular food products in Central Sulawesi is shredded beef, and sometimes aspects of food quality and safety were not given attention by producers or consumers. The objective of the study is to identify the chemical, microbiological and antioxidant properties of shredded beef produced and circulated in Palu City. This study uses a complete randomized design with 8 samples and each sample were repeated three times so that 24 samples were obtained with observed parameters including moisture content, ash content, protein content, fat content, total microbial count and antioxidant activity.The results showed that water content (5,04 -9,35%), ash content (3,59 - 5,74%), protein content (25,60-38,97%), fat content (19,20- 39,37%) and total microbial count (1,27-8,48 log cfu / g) and antioxidant activity as indicated by Inhibition Concentration / IC50 (3234,31 - 6740,5 ppm) and percentage of inhibition (35,63 - 80.27%). The results of this study indicate that shredded beef from various SMEs in the city of Palu is still partially met the quality standards based on SNI, so MSME guidance is needed periodically and continuously.